Manual on the new government accounting system for national government agencies. - Philippines. Commission on Audit (Quezon City Materials Development and Production Division Professional Development Center, Commission on Audit, 2002)
Details concepts, guidelines, and procedures for recording transactions and producing financial reports in government. This manual is recommended for use by government officials and personnel.
v.1 Accounting policies -- v.2 Accounting books, registries, records, forms and reports --v.3 The chart of accounts.
Keywords: Finance, Public -- Accounting -- Philippines -- Handbooks, manuals, etc